Risk factors for venous thromboembolism in women under combined oral contraceptive - Suchon, Pierre; Frouh, Fadi Al; Henneuse, Agathe; Ibrahim, Manal; Brunet, Dominique; Barthet, Marie-Christine; Aillaud, Marie-Françoise; Venton, Geoffroy; Alessi, Marie-Christine; Trégouët, David-Alexandre; Morange, Pierre-Emmanuel (Thrombosis and Haemostasis, 2016)
Identifying women at risk of venous thromboembolism (VTE) is a major public health issue. The objective of this study was to identify environmental and genetic determinants of VTE risk in a large sample of women under combined oral contraceptives (COC). A total of 968 women who had had one event of VTE during COC use were compared to 874 women under COC but with no personal history of VTE. Clinical data were collected and a systematic thrombophilia screening was performed together with ABO blood group assessment. After adjusting for age, family history, and type and duration of COC use, main environmental determinants of VTE were smoking (odds ratio [OR] =1.65, 95 % confidence interval [1.30–2.10]) and a body mass index higher than 35 kg.m-2 (OR=3.46 [1.81–7.03]). In addition, severe inherited thrombophilia (OR=2.13 [1.32–3.51]) and non-O blood groups (OR=1.98 [1.57–2.49]) were strong genetic risk factors for VTE. Family history poorly predicted thrombophilia as its prevalence was similar in patients with or without first degree family history of VTE (29.3 % vs 23.9 %, p=0.09). In conclusion, this study confirms the influence of smoking and obesity and shows for the first time the impact of ABO blood group on the risk of VTE in women under COC. It also confirms the inaccuracy of the family history of VTE to detect inherited thrombophilia.
Keywords: Deep-vein thrombosis; oral contraceptives; thrombophilia